Understanding the reading practices of Fort Hare students - O'Shea, Cathy (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning, 2017)
Universities world-wide are battling to offer access to far greater numbers than ever before. The University of Fort Hare, specifically, is also part of a troubled South African education system and is located in a disadvantaged, rural area. The main aim of this study was to understand Fort Hare students' reading practices, as reported by the students themselves. This thesis used a framework of New Literacy Studies, which views student learning as a process of mastering discipline-specific, socially constructed norms and values, and sees the adopting of a literacy as including the adoption of an identity. Since discourse, in the NLS tradition, has been found to be a mediating mechanism in the social construction of identity, a critical discourse analysis was adopted to begin understanding aspects of Fort Hare students' reading practices and the links between these and their identities. Critical realism is the ontological underpinning of this thesis. This means that the study aimed to identify the tendencies of certain mechanisms - in this case, Discourses - to affect students' reading practices, by analysing interview transcripts of focus group discussions held with 30 students. Frameworks and tools provided by Fairclough and Gee were applied to interview data analysis. The 'We blacks' Discourse was one of one of the prominent Discourses that interviewees drew on when talking about their reading practices. It was closely allied to the 'Resistance to reading' Discourse, as participants explained that they tended to disregard books and did not enjoy reading for leisure. The 'We blacks' Discourse in this way homogenised class and other differences between black students, and indicated the ways in which their experiences were outside of academic Discourses. This Discourse served as a constraining mechanism for some, and indicated that those who used it tended not to identify with the academy. There was an evident link between the 'We blacks' Discourse, the 'Resistance to reading' Discourse and the 'Better than us' Discourse, in which students who enjoyed reading were called names for supposedly being conceited. Two opposing discourses (with a small 'd') emerged when students talked about literacy sponsors like parents and lecturers. Some used the 'Our parents don't chase us' discourse to depict family members who were not encouraging, overlapping with the 'We blacks' Discourse. The contrasting 'Go read anything' discourse described more encouraging teachers and relatives. This discourse was also used to describe educators who had forced them to read, with several interviewees describing corporal punishment as being a necessary part of school-based literacy practices. It also became clear that Fort Hare's institutional identity played a role in some interviewees' self-identities, as the 'Resistance to reading' Discourse was linked to the 'Why bother?' Discourse. The latter seemed part of a defensive positionality that arose partly because some students see Fort Hare as a university with relatively low academic standards. However, the implication is that lecturers and others can work towards changing Discourses and so endeavour to enable reading practices. Educators could also take steps to address resistant attitudes and encourage reading.
Keywords: Uncatalogued